ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Rini Oktaviani Putri; Asep Sahrul Gunawan (STKIP Subang, 2026)
Character education based on Pancasila in elementary schools is an important foundation in shaping a generation with noble morals, integrity, and a strong sense of nationalism. This study aims to analyze the implementation of Pancasila values in learning at the elementary school level, specifically through the subject of Pancasila and Citizenship Education (PPKn). The research method uses a descriptive qualitative approach with observation, interviews, and documentation techniques with teachers and fifth-grade students at a public elementary school. The analysis results show that character education implementation is carried out through three main stages: planning, implementation, and evaluation. In the planning stage, teachers have integrated Pancasila values into the Lesson Plan (RPP), although it is still limited to normative aspects. The implementation stage is seen in learning activities that emphasize the values of mutual cooperation, discipline, and attitudes.